Relationship between tourism and economic growth a granger causality panel data approach - ÇAĞLAYAN AKAY, EBRU; ŞAK, NAZAN (My University, 2012)
This paper investigated the causal relationship between tourism revenue and gross domestic product (GDP) using the panel data of 135 countries for the period 1995–2008. For this purpose, Panel Granger causality analysis was applied to 11 groups of countries. This classification was created as America (30 countries), Asia (34 countries), Europe (37 countries), East Asia (13 countries), South Asia (6 countries), Central Asia (5 countries), Latin America & Caribbean (28 countries), Oceania (7 countries), Middle East & North Africa (11 countries), Sub Saharan Africa (24 countries) and the world (135 countries). Results indicated bidirectional causality in Europe between tourism revenue (TR) and gross domestic product (GDP). Findings showed that there is a unidirectional causality in America, Latin America & Caribbean and World from GDP to tourism revenue. While in case of East Asia, South Asia and Oceania the reverse direction of causality was found from tourism revenue to GDP. No causal relationship was found in Asia, Middle East and North Africa, Central Asia and Sub Saharan Africa.
Keywords: Sosyal ve Beşeri Bilimler; Ekonometri; Social Sciences and Humanities; Econometrics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Tourism Income; Economic Growth; Panel Unit Root; Panel Causality